Vulnerabilidade às IST/AIDS : desenvolvimento e validação de um instrumento de avaliação inspirado nas questões sociocientíficas - Alves, Manoel Messias Santos (2019)
We aim to discuss in this study on Sexually Transmissible Infections (STI) in a socioecological approach to health, considering its relevance to the emancipation of the students acting in the sociopolitical and ecological context of which they are part, as well as their relations with education in Science, Technology, Society and Environment (STSE). Therefore, the proposed general objective was to analyze the process of construction and validation of a school evaluation instrument in sciences involving conceptual, procedural and attitudinal aspects about the relation of quality of life and vulnerability to STI/AIDS, for high school students. Thus, recognizing the importance of considering students' performance as an indication of the quality of education, the evaluation tool was developed based on an attempt to approach with some characteristics of socio-scientific questions (SSI), such as the political dimension, presentation of controversies, decision making based on ethical, political and / or moral values and a content approach in the conceptual, procedural and attitudinal dimensions. In fact, in order for an instrument to collect data to document information in an objective and systematic way, it is essential that it be developed with quality, for this reason, the questionnaire was submitted to some validation processes. In this study we opted for content validation, in which we have the collaboration of a panel of specialists, formed by a multiprofessional team of educators, researchers and health professionals to evaluate the instrument and thus guarantee higher quality, credibility and precision of the criteria measured. We also performed a semantic evaluation of the questionnaire with a sample of students representing the subjects of the research, and after the necessary adjustments, we conducted a pilot test with 103 students of the 3rd year of high school, from state schools in Aracaju. The data produced were processed and analyzed statistically using the software Statistical Package for Social Science (SPSS). The Cronbach Alpha coefficient showed that the instrument had satisfactory internal consistency. For correlation analysis was applied Spearman's Rho coefficient between these variables and as a result we obtain evidence of significant correlation only between the variable "vulnerability" to the variable "psychological factors" with negative incidence -0.328 (sig = 0.028) . In general, the results indicate that the majority of the students who participated in the pilot study of this research did not show indicatives of vulnerability according to the established categories. Thus, the present study proved to be relevant from the technological point of view, since it is proposed to construct and validate a performance test capable of measuring vulnerability indicators and their relationship with quality of life; as also presented scientific and educational importance, as it sought to correlate quality life and vulnerability, and although it has not found a direct correlation between these variables with the respondent public perceives an important correlation between psychological quality of life and vulnerability, pointing a aimed at teachers, technicians and school supervisors to work with approaches to prevention of STIs, prioritizing, among other issues, actions that provide psychological stability to students.